Orthogonally modulated molecular transport junctions for resettable electronic logic gates - Meng, Fanben (2018)
Individual molecules have been demonstrated to exhibit promising applications as functional components in the fabrication of computing nanocircuits. Based on their advantage in chemical tailorability, many molecular devices with advanced electronic functions have been developed, which can be further modulated by the introduction of external stimuli. Here, orthogonally modulated molecular transport junctions are achieved via chemically fabricated nanogaps functionalized with dithienylethene units bearing organometallic ruthenium fragments. The addressable and stepwise control of molecular isomerization can be repeatedly and reversibly completed with a judicious use of the orthogonal optical and electrochemical stimuli to reach the controllable switching of conductivity between two distinct states. These photo-/electro-cooperative nanodevices can be applied as resettable electronic logic gates for Boolean computing, such as a two-input OR and a three-input AND-OR. The proof-of-concept of such logic gates demonstrates the possibility to develop multifunctional molecular devices by rational chemical design.